Modeling Rheotaxis based on Preference to Predict Fish Migration Behavior in A River - Febrina, Rina (MEDIA KOMUNIKASI TEKNIK SIPIL, 2016)
In this research, we attempt to determine preference of rheotaxis and estimated weight values in laboratory experiments using adult and juvenile ayu (Plecoglossus altivelis altivelis). We conducted paired comparisons of ayu distribution between the upper and lower sections of a test watercourse using several velocity conditions (10, 30, and 40 cm/s for juveniles; 20, 30, 50, 70, and 90 cm/s for adults). In upper watercourse sections, juvenile ayu preferred velocities of 30 cm/s and 40 cm/s, and adults preferred a velocity of 50 cm/s. Even when a highly preferred illumination condition of 4000 lux was present in the lower section, fish maintained a higher distribution in the upper section. We design a procedure to calculate rheotaxis preference and built it into our fish behavior simulation model on geographic information system (GIS) software. The model successfully predicted natural migration behavior of fish.